Validation of Antenna Modeling Methodology in IMT-Advanced Channel Model - Jianhua Zhang; Chun Pan (International Journal of Antennas and Propagation)
In this paper, the antenna modeling method in the International Mobile Telecommunications-Advanced (IMT-Advanced) channel model is validated by field channel measurements in the indoor scenario at 2.35 GHz. First, the 2 × 2 MIMO channel impulse responses (CIRs) are recorded with practical antennas as references. Second, the CIRs are reconstructed from the available IMT-Advanced channel model with field patterns of the practical antennas and updated spatial parameters extracted from the similar scenario measurements. Then comparisons between the field CIRs and the reconstructed CIRs are made from coherent bandwidth, eigenvalue dispersion, outage capacity, and ergodic channel capacity. It is found that the reconstructed results closely approximate real results in the coherent bandwidth and correctly describe the statistical characteristics in frequency domain. Compared to the field CIRs, the spatial correlation of the reconstructed CIRs with both types of antenna have a wider range that causes the underestimation of the 5% channel outage capacity. Due to the negligence of the coupling among the antennas and the near field effect of antenna, this modeling method will have a great impact on the characteristics of radio channels, especially on the spatial characteristics.